The Counselor Ideal Character Based on the Values of the Madurese Work Ethic - Ach. Sudrajad Nurismawan; Wasilatur Rahmah Siftia Rusydi; Nurasih Basri; Dyah Nopitasari; Najlatun Naqiyah (Bisma The Journal of Counseling, 2023)
Several regions in Indonesia that have good work ethic values, the Madura region also has a variety of work ethic values that are full of meaning and good for application in their respective professional fields. Unfortunately, to this day most ordinary people are more focused on a small number of problems that appear in the media related to Madurese society. Therefore, this study aims to analyze the concept of the ideal character of counselors based on the values of the Madurese work ethic as an effort to improve the professional competence of school counselors in providing assistance services to students at school. This study use qualitative research, Paul Ricoeur's hermeneutic approach which includes a variant of discourse analysis to interpret the message structure and the various functions of language stored in the Madurese Tor-cator (philosophical words). The main data is comes from the results of a previous study then strengthened through observation and field interviews. This study shows that the work ethic values of the Madura Tor-cator are very relevant to the professional orientation of school counselors. The results of this study provide an important contribution to enrichment materials for increasing the competence of school counselors based on regional local wisdom values.